Generation of Spatially Aligned Collagen Fiber Networks Through Microtransfer Molding. Issue 3 (29th August 2013) - Naik, Nisarga; Caves, Jeffrey; Chaikof, Elliot L.; Allen, Mark G.
<x xml:space="preserve">Abstract</x> The unique biomechanical properties of native tissue are governed by the organization and composition of integrated collagen and elastin networks. An approach for fabricating spatially aligned, fiber‐reinforced composites with adjustable collagen fiber dimensions, layouts, and distribution within an elastin‐like protein matrix yielding a biocomposite with controllable mechanical responses is reported. Microtransfer molding is employed for the fabrication of hollow and solid collagen fibers with straight or crimped fiber geometries. Collagen fibers (width: 2–50 μm, thickness: 300 nm to 3 μm) exhibit a Young's modulus of 126 ± 61 MPa and an ultimate tensile strength of 7 ± 3.2 MPa. As fiber networks within composite structures, straight fiber layouts display orthotropic responses with Young's modulus ranging from 0.95 ± 0.35 to 10.4 ± 0.5 MPa and tensile strength from 0.22 ± 0.08 to 0.87 ± 0.5 MPa with increasing fraction of collagen fibers (1–10%, v/v). In contrast, composites based on crimped fiber layouts exhibit strain‐dependent stiffness with an increase in Young's modulus from 0.7 ± 0.14 MPa to 3.15 ± 0.49 MPa, at a specific transition strain. Through controlling the microstructure of engineered collagen fiber networks, a facile means is established to control macroscale mechanical responses of composite protein‐based materials.